A Review of Determinants of Financial Inclusion - Abel, Sanderson; Mutandwa, Learnmore; Le Roux, Pierre (International Journal of Economics and Financial Issues, 2018)
The role of financial inclusion in the economic and financial discourse has gained a lot of interest both among academia and practitioners. The discussion has further received attention from development partners such as the World Bank, International Monetary Fund, G20 and AFDB among others. Taking cue from developments elsewhere Zimbabwean government commissioned the national financial inclusion strategy. The objective of the current study is to evaluate determinants of financial inclusion in Zimbabwe. The study established that age, education, financial literacy, income, and internet connectivity are positively related to financial inclusion. On the other hand the documentation required to open bank accounts and the distance to the nearest access point are negatively related to financial inclusion. The study recommends that the government should put in place policies that encourage financial service providers to set up their operations closer to the people or ensure they adopt technologies that ensure financial services are more accessible such as agency and mobile banking. The government should therefore encourage the use of KYC lite accounts to ease documentation requirements without compromising anti-money laundering framework which can destabilise the financial system. Keywords: Financial Inclusion, Financial Discourse, Financial System JEL Classifications: C23, E62, F30, D14, G21